Effect of Different Stocking Density on the Growth of Catfish (Clarias gariepinus) in Aquaponics Budikdamber System - Yopie Ryan Audy Harahap; Pande Gde Sasmita Julyantoro; Ayu Putu Wiweka Krisna Dewi (Advances in Tropical Biodiversity and Environmental Sciences, 2023)
Budikdamber (fish farming in buckets) is an innovation from the aquaponics system that is carried out to keep catfish (C. gariepinus) and plants in the same container. In the Budikdamber system, it is important to pay attention to the high and low density of fish stocking because the rearing container used is a bucket. The purpose of this research was to determine the growth rate and survival rate of catfish at different stocking densities. This research was conducted with 3 treatments and each treatment had 3 repetitions, treatment A (40 fish/m3), treatment B (80 fish/m3), and treatment C (120 fish/m3). The observations showed that the highest specific growth rate of catfish was found in treatment A with a value of 12.74%, followed by treatment B 12.55% and treatment C 12.20%. The highest survival rate of catfish was found in treatment A, which was 90.8%, followed by treatment B at 87.9%, and treatment C at 86.7%. The highest feed conversion ratio (FCR) of catfish was found in treatment B, which was 0.475, followed by treatment A at 0.445, and the lowest FCR value was found in treatment C, which was 0.368. Water quality parameters measured during observations included dissolved oxygen (DO), temperature, acidity (pH), nitrite and nitrate, where all water quality parameters were still considered optimal for growth and survival of catfish.